2020
DOI: 10.1186/s12974-020-01909-y
|View full text |Cite
|
Sign up to set email alerts
|

Chitotriosidase, a biomarker of amyotrophic lateral sclerosis, accentuates neurodegeneration in spinal motor neurons through neuroinflammation

Abstract: Background: Cerebrospinal fluid from amyotrophic lateral sclerosis patients (ALS-CSF) induces neurodegenerative changes in motor neurons and gliosis in sporadic ALS models. Search for identification of toxic factor(s) in CSF revealed an enhancement in the level and enzyme activity of chitotriosidase (CHIT-1). Here, we have investigated its upregulation in a large cohort of samples and more importantly its role in ALS pathogenesis in a rat model. Methods: CHIT-1 level in CSF samples from ALS (n = 158), non-ALS … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 48 publications
2
23
1
Order By: Relevance
“…Proteomic analysis found CHIT-1 to be significantly upregulated in ALS-CSF compared to control CSF, suggesting its possible role as a biomarker ( Varghese et al, 2013 ). This was subsequently substantiated by findings from the same group demonstrating its high specificity and sensitivity as a diagnostic biomarker ( Varghese et al, 2020 ). It is worth commenting that the function of CHIT-1 in the human nervous system has still not been established, with CHIT-1 also being implicated in other neurodegenerative diseases, such as Alzheimer’s disease and multiple sclerosis ( Varghese et al, 2020 ).…”
Section: Glial Contributions To Csf-mediated Neurodegenerationmentioning
confidence: 78%
See 2 more Smart Citations
“…Proteomic analysis found CHIT-1 to be significantly upregulated in ALS-CSF compared to control CSF, suggesting its possible role as a biomarker ( Varghese et al, 2013 ). This was subsequently substantiated by findings from the same group demonstrating its high specificity and sensitivity as a diagnostic biomarker ( Varghese et al, 2020 ). It is worth commenting that the function of CHIT-1 in the human nervous system has still not been established, with CHIT-1 also being implicated in other neurodegenerative diseases, such as Alzheimer’s disease and multiple sclerosis ( Varghese et al, 2020 ).…”
Section: Glial Contributions To Csf-mediated Neurodegenerationmentioning
confidence: 78%
“…Although many potentially toxic factors have emerged from studying the effects of ALS-CSF on glial cells, chitotriosidase-1 (CHIT-1), an inflammatory product specific to microglia, has been proposed to play a particularly important role in CSF-mediated neurodegeneration ( Varghese et al, 2020 ). Proteomic analysis found CHIT-1 to be significantly upregulated in ALS-CSF compared to control CSF, suggesting its possible role as a biomarker ( Varghese et al, 2013 ).…”
Section: Glial Contributions To Csf-mediated Neurodegenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a "feed-forward" loop wherein the chitinases sustain neuroinflammation in ALS via their autoand paracrine effects has already been postulated (12). For instance, Varghese et al demonstrated that microglia appear to be the primary cellular source for CHIT1 in the CNS using murine cultures and that microglia themselves were susceptible to the effects of accumulated CHIT1, as they were chronically activated as a result of exposure (11). Another study also showed that conditioned medium from MoMas induced CHI3L1 transcription and morphological changes in cultured human astrocytes (19).…”
Section: Discussionmentioning
confidence: 99%
“…In ALS, these moieties exacerbate neuroinflammation and directly affect neuronal viability (11)(12)(13). While studies using post-mortem motor cortex and spinal cord tissue from ALS patients have reported micro-and astroglial expression of CHIT1 and CHI3L1, respectively, the cellular origins of these targets remain to be fully understood.…”
Section: Introductionmentioning
confidence: 99%